Pengaruh Return on Assets, Current Ratio, Debt to Equity Ratio dan Total Assets Turnover terhadap Price to Book Value: - Mutiara, Mirza Rizki; Thamrin, Kemas Muhammad Husni; Andriana, Isni (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to empirically examine and analyze the effect of Return On Assets, Current Ratio, Debt To Equity Ratio and Total Assets Turnover on Price to Book Value. The data was taken using secondary data from the Indonesia Stock Exchange through financial reports and it was analysed using multiple linear regression. The sampling technique used a purposive sampling method with a total sample of 21 mining sector companies listed on the Indonesia Stock Exchange in 2017-2021. “The results showed that Return On Assets, Current Ratio and Total Assets Turnover had a positive and significant effect on Price to Book Value. Meanwhile, the Debt to Equity Ratio has no significant effect on the Price to Book Value in mining sector companies listed on the Indonesia Stock Exchange in 2017-2021.